SASTRA SUFISTIK MELAYU DAN SUNDA DI NUSANTARA: MEMPERTEMUKAN HAMZAH FANSURI DAN HAJI HASAN MUSTAPA - Jajang A. Rohmana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2015)
This article is aimed at analyzing the use of local symbols in Sufism literature in Nusantara. The objects of this study are Hamzah Fansuri’s poems and Haji Hasan Mustapa’s Sufism poems. Both writers were not only the biggest poets but also controversial in two different regions, Malay and Sunda. The analysis used in this study was semantic and intertextual approaches. This study found that there are five similarities between these two writers. First, both writers used poems as a spiritual expression of philosophical Sufism. Second, one of them used local symbolic image of Melayu coastal environment and the other used Pasundan mountainous nature. Third, both of them used poems as biographical expressions. Fourth, they both used quotations of verses or hadits in their poems. The fifth, they both criticized the breakage of Islamic law (syariah). This study shows that Hamzah and Mustapa tended to bephilosophical Sufism without ignoring syariah. For that reason, both the criticism of al-Raniri towards Hamzah and one of Sayyid ‘Utsman towards Mustapa are not really appropriate. The differenti ation between the creator and the creature in local symbols of Malay and Sunda clearly shows the continuous influence of neo-Sufism on Muslim intellectuals networkingalong Indonesian Archipelago since 6th century. This study is significant to show that indigenization of Sufism in Indonesian archipelago can be seen in the use of various Sufism symbols, which reflect the background of its nature and culture. This also shows that distinction of Nusantara Islam mysticism identity cannot be separated from great narration of Sufism tradition in the world. In addition, this study strengthens the importance of interconnection between Islam of different culture in two different regions, Malay and Sunda.